Kualitas Pelayanan Publik - Badjeber, Fikran; Aneta, Asna; Mozin, Sri Yulianty (Jambura Journal of Administration and Public Service, 2025)
This study aims to determine, describe, and analyze the quality of public service at the Department of Education and Culture of Gorontalo City. The approach used in this study is qualitative. The research method is descriptive qualitative. Data collection was conducted through interviews, observations, and documentation studies. Data analysis techniques in this study were carried out through data reduction, data presentation, and conclusion drawing/verification. The main focus of this study is to determine the extent to which the quality of service provided meets the expectations of the public based on the SERVQUAL dimensions, which include tangibles, reliability, responsiveness, assurance, and empathy. However, there are still several obstacles in the public service quality at the Department of Education and Culture of Gorontalo City, such as improvements in human resource management, enhancing communication and empathy training for employees, and clarifying service procedures to reduce uncertainties felt by service users. The improvement of public service quality is expected to increase user satisfaction and build better trust in government institutions.